Seismic Performance of Multistorey Masonry Structure with Openings Repaired with CFRP Grid. (8th May 2018) - Gu, Jin-Ben; Tao, Yi; Xin, Ren; Yang, Z.; Shi, Qing-Xuan
Abstract : FRP composites have been used for strengthening RC and masonry structures for decades. However, the researches on repairing multistorey masonry structures using FRP grids were relative less. In the present paper, an experimental study on the seismic performance of multistorey masonry structure with openings repaired with CFRP grid is introduced. Specifically, a 1/3-scale three-floor masonry wall with window openings was tested under quasistatic action to simulate the seismic damages. The damaged masonry wall was then repaired by externally bonding CFRP grids to the areas where the cracks intensively occurred. The repaired masonry wall was retested under the same loading to investigate the seismic resistance and assess the recovery attributed from the CFRP grid repairing. The findings of this study showed that CFRP grid repairing could effectively postpone or even prevent the occurrence and development of cracking. The seismic resistance of the masonry, including shear capacity, energy dissipation capacity, deformability, stiffness degradation, and ductility, was restored. The application of CFRP grid may shift the failure mechanism of the multistorey masonry wall. The recommendation of repair scheme for the similar structures was also proposed in accordance with the findings of the present work.